Characterization of genetic and biochemical mechanisms of fludioxonil and pyrimethanil resistance in field isolates of Penicillium digitatum - Forster, Helga; Jones, Carol; Kanetis, Loukas (My University, 2008)
Genetic and biochemical mechanisms of fludioxonil and pyrimethanil resistance in isolates of Penicillium digitatum were evaluated and compared to those characterized in other fungi. Resistant isolates were naturally occurring in packinghouses and were not associated with crop losses. For the phenylpyrrole fludioxonil, EC 50 values were 0.02 to 0.04 μg/ml for sensitive, 0.08 to 0.65 μg/ml for moderately resistant (MR), and >40 μg/ml for highly resistant (HR) isolates. Two fludioxonil-sensitive isolates evaluated were also significantly more sensitive to the unrelated dicarboximide fungicide iprodione, that also disrupts osmotic regulation, than the MR and HR isolates. There was no consistent relationship, however, between the HR and MR isolates and their sensitivity to iprodione or osmotic stress. Although, two nucleotide substitutions were found in a sequence analysis of the N-terminal amino acid repeat region of the os-1-related histidine kinase gene among isolates of P. digitatum, these were not correlated with fludioxonil resistance. In mycelia not exposed to fludioxonil, the amount of phosphorylated OS-2-related protein (PdOS-2) was higher in fludioxonil-sensitive isolates and lowest in the HR isolate. An increase in PdOS-2 was observed for sensitive and resistant isolates after exposure to fludioxonil. In addition, glycerol content in untreated mycelia of the fludioxonil-sensitive isolate was significantly higher than in resistant isolates. After exposure to fludioxonil, glycerol concentrations significantly increased in the sensitive and MR isolates, but not in the HR isolate. Thus, our studies indicate that the mode of action of fludioxonil in P. digitatum is probably the mitogen-activated protein kinase pathway that stimulates glycerol synthesis in sensitive and MR isolates. The general suppression of this pathway in resistant isolates was supported by the fact that growth and sporulation of MR and HR isolates were significantly reduced from that of sensitive isolates. In studies on the mode of action of anilinopyrimidines (AP), EC50 values for mycelial growth of P. digitatum and the previously characterized Botrytis cinerea were determined for cyprodinil and pyrimethanil using a defined culture medium without and with the addition of selected amino acids and homocysteine. The addition of amino acids resulted in a reduced toxicity of the two AP fungicides in both fungi, but the effect of each additive was significantly lower for P. digitatum than for B. cinerea. This suggests that methionine biosynthesis is not the primary target site of APs in P. digitatum
Keywords: Citrus; Fungicide resistance; Fungal proteins; Pyrroles; Amino acid sequence; Plant diseases; Pyrimidines